2018
DOI: 10.1109/jsen.2017.2782181
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bayesian Recognition of Locomotion and Gait Phases With Wearable Sensors

Abstract: /0000-0002-9922-7912, Mahmood, I and Dehghani-Sanij, AA (2018) Simultaneous Bayesian recognition of locomotion and gait phases with wearable sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…The participants were instructed to walk a forty-meter flat ground four times, and then walked back and forth twenty times on a slope with a length of 5 m angled at 5.2 degrees. Similar ramp angle degrees are also found in other relevant studies and they are summarized in Table 2 for comparison with our work [19,22,27,31,35]. Table 2.…”
Section: Experiments Setupsupporting
confidence: 88%
See 1 more Smart Citation
“…The participants were instructed to walk a forty-meter flat ground four times, and then walked back and forth twenty times on a slope with a length of 5 m angled at 5.2 degrees. Similar ramp angle degrees are also found in other relevant studies and they are summarized in Table 2 for comparison with our work [19,22,27,31,35]. Table 2.…”
Section: Experiments Setupsupporting
confidence: 88%
“…In [19], a terrain identification-enabled exoskeleton system which integrated only two attitude and heading reference system (AHRS) sensors and three GRF sensors was designed, tested by three healthy subjects and successfully identified ramp and level ground, with a mean accuracy of 97.77%. The number and categories of the applied sensors and the classification accuracy of the above studies, along with some other relevant studies [17,[33][34][35], are summarized in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Yuwono et al [18] presented a single IMU system that identifies bilateral heel-strike events with the use of the Bayesian method. Martinez-Hernandez et al [11] proposed a Bayesian formulation to achieve high recognition accuracy of simultaneous daily activities and gait phases recognition with a small number of sensors.…”
Section: Related Workmentioning
confidence: 99%
“…Results showed that the closed-loop approach would facilitate the adaptation from patient to patient. A multilayer architecture is recognised to be essential for intelligent systems to perform robust data processing, perception, and action at different levels of abstraction [11]. Our work could be extended to include the high and low-level process of robotic control in real-time.…”
Section: Accuracy Of Ankle Angle Measurementmentioning
confidence: 99%
See 1 more Smart Citation